(Effects of Hydrocolloid Types on Texture Characteristics of Black of Black Cincau Gel) - Dhiah Nuraini; Dedi Fardiaz; Ni Luh Puspitasari; Atjeng M. Syarief (Balai Besar Industri Agro, 2000)
The experiment was aimed to observed effects of type and amount of added hydrocolloids to texture characteristic of black cincau gel prepared from gel froming compound powder. three types of hydrocolloids added are arabic gum, kappa-carrageenan, and alginic acid. the texture characteristic observed were included breaking point, breaking strength, rigidity, height decrease and syneresis. The result showed that arabic gum and alginic acid has synergistic effect in black cincau gel formulation, while kappa-carrageenan has antagonistic one. the addition of arabic gum resulted in the lowest values of rigidity, height, and syneresis at addition level of 5 per cent. on the contrary, addition of kappacarrageenan resulted gel with breaking point, breaking strenght, and heihgt decrease which decreases with the increasing of addition. while addition of alginic acid produced gel with various texture characterics, depended on the level of addition.